The contribution of hyperinsulinemia to the hyperandrogenism of polycystic ovary syndrome - Nadia B. Pateguana; Alvin Janes (Journal of Metabolic Health, 2019)
Background: Polycystic Ovary Syndrome (PCOS) is a very common endocrine disorder of young women.